1996
DOI: 10.1051/lait:1996425
|View full text |Cite
|
Sign up to set email alerts
|

Le goût des acides aminés, des peptides et des protéines : exemple de peptides sapides dans les hydrolysats de caséines

Abstract: Résumé -Après quelques définitions et un bref rappel sur la physiologie du goût, cette revue s'attache à décrire les connaissances actuelles sur le goût des acides aminés et des peptides. En s'appuyant sur la théorie des cinq goûts (amer, sucré, salé, acide, umami), nous avons tenté de décrire dans chaque cas la relation structure-goût. Nous avons regroupé, sous forme de tableaux, les peptides développant une saveur en solution, ainsi que leurs seuils de détection. Le cas des hydrolysats de caséines est dévelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
4

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 56 publications
(75 reference statements)
0
11
0
4
Order By: Relevance
“…Thus, these strains had the highest capacity for proteolysis, which is an important process in cheesemaking. Indeed, proteolysis contributes to the development of cheese texture, flavors and aromas (Ardö et al, 2017;Andersen et al, 2010;McSweeney, 1997;Roudot-Algaron, 1996;Ardö, 2006). Previous measurements of proteolytic activity in synthetic media detected significant differences between P. roqueforti populations, but not between the two cheese populations (Dumas et al, 2020).…”
Section: Based On Chemical Analyses and Powerful Chromatographic Discmentioning
confidence: 99%
“…Thus, these strains had the highest capacity for proteolysis, which is an important process in cheesemaking. Indeed, proteolysis contributes to the development of cheese texture, flavors and aromas (Ardö et al, 2017;Andersen et al, 2010;McSweeney, 1997;Roudot-Algaron, 1996;Ardö, 2006). Previous measurements of proteolytic activity in synthetic media detected significant differences between P. roqueforti populations, but not between the two cheese populations (Dumas et al, 2020).…”
Section: Based On Chemical Analyses and Powerful Chromatographic Discmentioning
confidence: 99%
“…Since higher levels of hydrophobic peptides have been detected in bitter cheeses, the prevalence of the hydrophobic over hydrophilic oligopeptides could generate bitterness during cheese ripening. Bitterness, one of the most common cheese offflavours (Lemieux & Simard, 1992;Visser, Slangen, Hup & Stadhouders, 1983), is directly related to formation of peptides having well-defined structure (Roudot-Algaron, 1996). For instance the bitter peptide b- , formed by the action of rennet and starter organisms, has been recognised as a major cause of bitterness in Gouda cheese (Stadhouders, Hup, Exterkate, & Visser, 1983;Visser et al, 1983) as well as in Cheddar cheese (Pouchards, Lemieux, & Simard, 1989).…”
Section: Casein Oligopeptides Produced During Cheese Ripeningmentioning
confidence: 99%
“…More recently Sommerer and others (1998) concluded that small peptides had no effect on the taste of goat cheese. In addition, most of the low-molecularweight peptides, tasted as single compound from hydrolyzed casein or cheese, were described as bitter (Roudot-Algaron 1996). Although peptides have been thought to exhibit favorable flavor (van den Oord and van Waassenaar 1997), such peptides have not been reported in cheese so far.…”
Section: Significance On Tastementioning
confidence: 99%